Terminal Ligand and Packing Effects on Slow Relaxation in an Isostructural Set of [Dy(H2dapp)X2]+ Single Molecule Magnets. Issue 61 (14th October 2021) - Pfleger, Rouven F.; Schlittenhardt, Sören; Merkel, Marcel P.; Ruben, Mario; Fink, Karin; Anson, Christopher E.; Bendix, Jesper; Powell, Annie K.
Abstract: We report three structurally related single ion Dy compounds using the pentadentate ligand 2, 6‐bis(( E )‐1‐(2‐(pyridin‐2‐yl)‐hydrazineylidene)ethyl)pyridine (H2 dapp) [Dy(H2 dapp)(NO3 )2 ]NO3 (1 ), [Dy(H2 dapp)(OAc)2 ]Cl (2 ) and [Dy(H2 dapp)(NO3 )2 ]Cl0.92 (NO3 )0.08 (3 ). The (H2 dapp) occupies a helical twisted pentagonal equatorial arrangement with two anionic ligands in the axial positions. Further influence on the electronic and magnetic structure is provided by a closely associated counterion interacting with the central N−H group of the (H2 dapp). The slow relaxation of the magnetisation shows that the anionic acetates give the greatest slowing down of the magnetisation reversal. Further influence on the relaxation properties of compounds1 and 2 is the presence of short nitrate‐nitrate intermolecular ligand contact opening further lattice relaxation pathways. Abstract : Three new dysprosium complexes with a pentadentate ligand occupying five equatorial sites differ only in the nature of the axial ligands. These help tune the relaxation properties as judged by an analysis of the AC susceptibility data. More in depth analysis by using two recently suggested fitting equations lead to similar outcomes for all three systems. As a further contribution to the relaxation pathway involving the phonon bath it is concluded that a short nitrate‐nitrate interaction between molecules helps dampen the spin phonon coupling.